Silver Metallization Characterization and Resistivity Performance Potential toward Chemical Sensor Application - A. Bakar, Amnani; H. Hashim, Nor; A.Tajuddin, Hairul; Z. Sahdan, Mohd; A. Saparudin, Faiz (International Journal of Engineering and Technology, 2019)
Performance of limiting resistive and capacitive signal delays increases gradually depends on the complexity degree of multilayer metallization. Electrodes sensor for electrical applications requires low surface roughness and low resistivity metal layers. Amongst conductive metal series, silver (Ag) has the lowest resistivity. On the other hand, compared to aluminum and copper, this metal also has higher oxidation resistance. This study aims to characterize Ag thin film on the glass substrate and the resistivity performance by using a physical deposition technique for chemical sensor application. A series of Ag thin film with different thickness were prepared from thermal vacuum evaporator at 3.45 x 10-5 Pa with applied current at 28 Ampere in 21 minutes. Four-point resistivity probing instrument was used for resistivity testing of the thin films with different thickness. The prepared Ag thin film shows a low average roughness at 1.89 nm. A smooth and homogeneous of Ag thin film is an advantage to provide a sensitive surface for element recognition in the development of chemical sensor and an adsorbate can be justified whereas it schematically assembled with the arrangement onto smooth and perfectly flat thin film surface. Ag thin film has shown a crystallite size with respect to 50.84 nm. The low rough surfaces have fewer nucleation sites, therefore fewer grains (crystallites) will appear. The optimum thickness was determined at 107 nm and the resistivity of Ag thin film was an average at 1.988 x10-8 Ohm m.Â Â Â